Role of Digital Training and Intrinsic Motivation in Improving Elementary Teachers' Performance in Cipicung - Hidayat, Gilang Apriyana; Ihsan, Adi Muhammad Nur (INOVATOR, 2026)
In Indonesia, efforts to digitalize education are reflected in the implementation of the Merdeka Belajar program and the use of the Platform Merdeka Mengajar (PMM). However, the increased participation in digital training has not been fully accompanied by optimal improvements in teacher performance. In addition to digital training, internal psychological factors such as intrinsic motivation also play an important role in determining teacher performance. This study aims to examine the role of digital training and intrinsic motivation in improving the performance of elementary school teachers in Cipicung Village. This research adopts a positivist paradigm with a quantitative approach, using survey methods for data collection. The data were analyzed using multiple linear The findings reveal that both digital training and intrinsic motivation have a positive effect on the performance of elementary school teachers in Cipicung Village. Furthermore, intrinsic motivation is identified as the more dominant factor influencing teacher performance.